Frequency regulation in adaptive virtual inertia and power reserve control with high PV penetration by probabilistic forecasting - Chang, Jiaming; Du, Yang; Chen, Xiaoyang; Lim, Enggee; Wen, Huiqing; Li, Xingshuo; Jiang, Lin (Frontiers in Energy Research, 2022)
The large-scale deployment of sustainable energy sources has become a mandatory goal to reduce pollution from electricity production. As photovoltaic (PV) plants replace conventional synchronous generators (SGs), the significant inherent rotational inertia characteristics are reduced. The high penetration of PV results in reduced system inertia, leading to system frequency instability. Virtual inertial control (VIC) technology has attracted increasing interest because of its ability to mimic inertia. An energy storage system (ESS) can be used to provide virtual inertia. However, the ESS adoption is hindered by the high cost. PV can provide virtual inertia by reserving power using forecasted results. The determined forecast gives PV the ability to reserve power to increase system inertia. Nevertheless, it has forecast errors and energy waste in a stable state. This paper proposes an adaptive forecasting-based (AFB) VIC method to increase system stability using probabilistic forecasts. The adaptive power reserve and virtual inertia control are proposed to reduce energy waste and increase system inertia. The simulation results reveal that the proposed method has adaptive system inertia to reduce the reserved power, required ESS power capacity, and battery aging.